2021
DOI: 10.1001/jamaneurol.2020.4689
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Progressive Multiple Sclerosis From the Imaging Perspective

Abstract: agnetic resonance imaging (MRI) is central in the diagnostic workup of patients with suspected multiple sclerosis (MS) given its high sensitivity to detect disease dissemination in space and over time and its substantial, albeit imperfect, ability to exclude other mimics of MS. From 2001 until 2017, great effort was expended providing successive iterations of the McDonald criteria to define imaging features typical of MS in patients presenting with clinically isolated syndrome (CIS). 1 However, diagnosis of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 158 publications
3
37
0
1
Order By: Relevance
“…It is worth noting that 'MRI activity' (new T2 lesions) in patients aged over 55-60 is likely to be confounded by lesions that are not MSassociated but are due to the increasing number of comorbidities (especially cerebrovascular) in elderly populations (e.g. hypertension) (Filippi et al, 2020;Guisset et al, 2020). Insufficient reproducibility of longitudinal MRI findings (especially beyond approval studies) has long been known as a problem in MRI follow-up investigations among clinical neurologists (Molyneux et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that 'MRI activity' (new T2 lesions) in patients aged over 55-60 is likely to be confounded by lesions that are not MSassociated but are due to the increasing number of comorbidities (especially cerebrovascular) in elderly populations (e.g. hypertension) (Filippi et al, 2020;Guisset et al, 2020). Insufficient reproducibility of longitudinal MRI findings (especially beyond approval studies) has long been known as a problem in MRI follow-up investigations among clinical neurologists (Molyneux et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Since the accumulation of chronic active lesions may represent one of the contributors to clinical disability in PMS [9], the demonstration of a beneficial effect of ocrelizumab in limiting chronic inflammation, demyelination, and axonal loss could further support the use of this drug in limiting clinical worsening in these patients.…”
Section: Conventional T1-and T2-weighted Sequencesmentioning
confidence: 98%
“…dynamic contrast enhancement [DCE]), chronic active lesions, ~9.4% of all chronic lesions, showed no contrastenhancement, thus they lack substantially abnormal bloodbrain barrier permeability that typically characterizes acute lesions [7]. Iron rim lesions are also characterized by a more limited lesional repair and have been described in all MS phenotypes although with heterogeneous reported rates: clinically isolated syndrome/relapsing-remitting (RR) MS from 6% to 53%, PMS from 7% to 62% [3,4,8,9]. By evaluating the longitudinal evolution of iron rim lesions over up to 7 years, a recent study with the longest follow-up currently available showed that such lesions are characterized by a slow rate of increase in size in the first years after their formation and then stabilize.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance imaging can also support the identification of mechanisms behind disease progression, including paramagnetic rim lesions, subpial demyelination, distinct spinal cord pathology, and brain and spinal cord atrophy. 44 …”
Section: Magnetic Resonance Imaging In Multiple Sclerosis In the Clinical Settingmentioning
confidence: 99%